Smallholders’ choice of avocado marketing channels in Murang’a County, Kenya - Njuguna, Karing’u kelvin; Isaboke, Hezron Nyarindo; Ndirangu, Samuel Njiri (Machakos University Press, 2021)
However, smallholder avocado farmers have not benefited from this expansion in demand. This is attributed to use of non-performing marketing channels that does not link them to the high value markets. The purpose of this paper is to investigate the determinants of choice of avocado marketing channels in Murang’a County. Stratified sampling procedure was used to obtain a sample of 384 smallholder avocado farmers from the seven key producing areas of the County. Descriptive statistics and multinomial logit regression model were used for analysis, with marketing through farmer organizations being the reference marketing channel. Results of Multinomial regression analysis showed that the probability of choosing brokers was significantly affected by farm size, household head’s gender, education level of HHH, time taken to collect avocado, access to extension, farm income and intercropping avocado with coffee. Likewise probability of farmers’ decision on direct sales to market was influenced by off farm income, dairy cattle kept by the farmer, intercropping avocado with coffee, growing organic avocado, travelling costs to buyer locations, farmer organization membership fees and subscriptions. Trainings on avocado farming methods, time taken to collect avocados, delayed buying of avocados and off-farm income were among the factors that significantly affected the probability of choosing to market through local traders. Farm gate price reduced the likelihood of choosing brokers and direct sales. Enhancing adoption of organic avocado production technology would increase the likelihood of smallholders’ choice of export markets.
Keywords: Smallholders; Marketing channels; Multinomial logit model